Size Distribution and Estimated Respiratory Deposition of Total Chromium, Hexavalent Chromium, Manganese, and Nickel in Gas Metal Arc Welding Fume Aerosols - Cena, Lorenzo G. (Aerosol Sci Technol, 2014)
A laboratory study was conducted to determine the mass of total Cr, Cr(VI), Mn, and Ni in 15 size fractions for mild and stainless steel gas-metal arc welding (GMAW) fumes. Samples were collected using a nano multi orifice uniform deposition impactor (MOUDI) with polyvinyl chloride filters on each stage. The filters were analyzed by inductively coupled plasma mass spectrometry (ICP-MS) and ion chromatography. Limits of detection (LODs) and quantitation (LOQs) were experimentally calculated and percent recoveries were measured from spiked metals in solution and dry, certified welding-fume reference material. The fraction of Cr(VI) in total Cr was estimated by calculating the ratio of Cr(VI) to total Cr mass for each particle size range. Expected, regional deposition of each metal was estimated according to respiratory-deposition models. The weight percent (standard deviation) of Mn in mild steel fumes was 9.2% (6.8%). For stainless steel fumes, the weight percentages were 8.4% (5.4%) for total Cr, 12.2% (6.5%) for Mn, 2.1% (1.5%) for Ni and 0.5% (0.4%) for Cr(VI). All metals presented a fraction between 0.04 and 0.6 μm. Total Cr and Ni presented an additional fraction <0.03 μm. On average 6% of the Cr was found in the Cr(VI) valence state. There was no statistical difference between the smallest and largest mean Cr(VI) to total Cr mass ratio (p-value D 0.19), hence our analysis does not show that particle size affects the contribution of Cr(VI) to total Cr. The predicted total respiratory deposition for the metal particles was ∼25%. The sites of principal deposition were the head airways (7–10%) and the alveolar region (11–14%). Estimated Cr(VI) deposition was highest in the alveolar region (14%).